2007
DOI: 10.1212/01.wnl.0000266663.27398.9f
|View full text |Cite
|
Sign up to set email alerts
|

Blood harmane is correlated with cerebellar metabolism in essential tremor

Abstract: This study provides additional support for the emerging link between harmane, a neurotoxin, and ET. Further studies are warranted to address whether cerebellar harmane concentrations are associated with cerebellar pathology in postmortem studies of the ET brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…This correlation was not found in other brain regions (e.g., thalamus, basal ganglia) or with other neurotoxins (e.g., lead) [159]. These findings suggest that increased blood harmane concentration could be associated with greater cerebellar neuronal damage, consistent with the animal study data that harmane and other β-carboline alkaloids produce cerebellar damage [121, 126, 127, 138141].…”
Section: Possible Environmental Toxins In Etsupporting
confidence: 76%
See 1 more Smart Citation
“…This correlation was not found in other brain regions (e.g., thalamus, basal ganglia) or with other neurotoxins (e.g., lead) [159]. These findings suggest that increased blood harmane concentration could be associated with greater cerebellar neuronal damage, consistent with the animal study data that harmane and other β-carboline alkaloids produce cerebellar damage [121, 126, 127, 138141].…”
Section: Possible Environmental Toxins In Etsupporting
confidence: 76%
“…Using magnetic resonance spectroscopic imaging, Louis et al[159] also demonstrated a strong inverse correlation between cerebellar N -acetyl aspartate to creatine ratio (a marker of neuronal damage) and blood harmane concentrations (p = 0.009, adjusting for age and gender) in a small study of 12 ET cases. This correlation was not found in other brain regions (e.g., thalamus, basal ganglia) or with other neurotoxins (e.g., lead) [159].…”
Section: Possible Environmental Toxins In Etmentioning
confidence: 99%
“…(1-methyl-9H-pyrido- [3,4-b]-indole), a tremor-producing b-carboline alkaloid (Louis et al 2007), is naturally present in hallucinogenic plants, such as Peganum harmala Linn (Zygophyllaceae), Banisteriopsis caapi (Spruce ex Grisb.) Morton (Malpighiaceae), and Tribulus terrestris Linn (Zygophyllaceae).…”
Section: Harmanementioning
confidence: 99%
“…Although postmortem studies point towards cerebellar changes, PET and fMRI studies have revealed abnormalities in the cerebellum, thalamus, and triangle of Guillain-Mollaret, which is settled in the brain stem and inferior olive nucleus. Researchers argue that the postural tremor of ET arises from spontaneous firing of inferior olivary nucleus (ION), which connects the cerebellum and its output pathways to the cerebral cortex and then to the spinal cord through VIM of the thalamus (11,12,13,14,15,16,17). Studies have shown that ET amplitude could be significantly reduced with thalamic lesions or thalamic stimulation, and the thalamus has been suggested to play a major role in the formation or transmission of ET (18,19).…”
Section: Discussionmentioning
confidence: 99%